2014
DOI: 10.5194/acp-14-4409-2014
|View full text |Cite
|
Sign up to set email alerts
|

A case study of sea breeze blocking regulated by sea surface temperature along the English south coast

Abstract: Abstract. The sensitivity of sea breeze structure to sea surface temperature (SST) and coastal orography is investigated in convection-permitting Met Office Unified Model simulations of a case study along the south coast of England. Changes in SST of 1 K are shown to significantly modify the structure of the sea breeze immediately offshore. On the day of the case study, the sea breeze was partially blocked by coastal orography, particularly within Lyme Bay. The extent to which the flow is blocked depends stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The perturbation was largely confined to a 400 m layer to represent the onshore flow of shallow sea breeze circulation based on observations [Miller et al, 2003;Iwai et al, 2008;Sweeney et al, 2014].…”
Section: 1002/2016jd026247mentioning
confidence: 99%
See 1 more Smart Citation
“…The perturbation was largely confined to a 400 m layer to represent the onshore flow of shallow sea breeze circulation based on observations [Miller et al, 2003;Iwai et al, 2008;Sweeney et al, 2014].…”
Section: 1002/2016jd026247mentioning
confidence: 99%
“…Experiment shows that the simulation results were insensitive to the width of the transition area. The perturbation was largely confined to a 400 m layer to represent the onshore flow of shallow sea breeze circulation based on observations [ Miller et al ., ; Iwai et al ., ; Sweeney et al ., ].…”
Section: Configuration Of Numerical Model and Experimentsmentioning
confidence: 99%
“…A diagnostic study over the same region during late spring or early summer might be expected to exhibit stronger solenoidal forcing of sea-breeze circulations. Some preliminary modeling investigations of the role of water temperatures for lake breezes were reported by Arritt [41] and for sea breezes by Kawai et al [42] and Sweeney et al [43]. It is suggested that additional microscale diagnostic investigations of sea-breeze thermodynamic structure using mobile observing platforms should be pursued for a variety of geographic and synoptic conditions, in particular with regard to static stability, available moisture supply, land surface character, and topography.…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing the impact of atmosphere–ocean coupling on results, it is instructive to consider the sensitivity of fog development to the persisted SST used in atmosphere‐only mode for this case. Following the methodology adopted in a number of previous studies (for example, Sweeney et al , ; Bari et al , ), the persisted SST in the FIX_H configuration is incremented everywhere by a constant value of −2 K, −1 K, +1 K, or +2 K (Table ). The modified SST initial condition remains constant throughout each simulation.…”
Section: Sensitivity Of Sea‐fog Evolution To Persisted Sstmentioning
confidence: 99%
“…A diverse range of large-scale atmospheric processes can be impacted, including storm-track location (Brayshaw et al, 2011;Woollings et al, 2012), frontal propagation (Parfitt et al, 2016;Passalacqua et al, 2016) and precipitation (Minobe et al, 2008), the evolution of the Madden-Julian Oscillation (Seo et al, 2014;DeMott et al, 2015;Stan et al, 2018), the El Niño-Southern Oscillation (ENSO: for example, Ham et al, 2010;Masson et al, 2012), and Indian (for example, Terray et al, 2012) and Australian monsoon systems (Wang and Zang, 2017). The variation of SST has also been shown to impact more local-scale processes, including the development of boundary-layer cloud (for example, Fallmann et al, 2017), urban heat islands (Oda and Kanda, 2009), and sea-breeze circulations (for example, Sweeney et al, 2014;Lombardo et al, 2016). This article focuses on the impact of SST variability on the development of coastal and sea fog, using a high-resolution atmosphere-ocean-wave regional coupled prediction system.…”
Section: Introductionmentioning
confidence: 99%